Effectiveness of a Program to Improve Attention towards Affective-Sexual, Bodily and Gender Diversity in University Students - Francisco Manuel Morales-Rodríguez (MDPI AG, 2021)
It is necessary for the university environment to contribute to the improvement of the attention paid to affective-sexual, bodily, and gender diversity. This research deals with how, by means of a teaching innovation program, competences for affective-sexual diversity were developed. Specifically, negative attitudes towards diversity, knowledge, and degree of empathy on these issues before and after the implementation of the program are compared. The degree of satisfaction, perceived usefulness, and fulfillment of the objectives proposed in the program were also evaluated. An ex post facto design was used. The participants in this study were 129 students belonging to Educational Sciences and Psychology, out of 2400 who benefited from the innovation program. The results showed an increase in competences related to the attention to diversity, with the improvement of attitudes and knowledge about affective-sexual diversity after the application of the program. It is concluded that this type of innovation program, with quality training, contributes to the improvement of coexistence and the prevention of gender violence in university classrooms, eliminating stereotypes and negative attitudes towards diversity.